Game of thrones. The complete eighth season [videorecording (DVD)] - Nutter, David, 1960-; Sapochnik, Miguel; Dinklage, Peter; Headey, Lena; Clarke, Emilia, 1986-; Martin, George R. R. (HBO Home Entertainment, 2019)
Follows the adventures of the powerful families in the kingdom of Westeros that are constantly vying for control of the throne.